1994
DOI: 10.1002/ana.410360404
|View full text |Cite
|
Sign up to set email alerts
|

Viability thresholds and the penumbra of focal ischemia

Abstract: The classic concept of the viability thresholds of ischemia differentiates between two critical flow rates, the threshold of electrical failure and the threshold of membrane failure. These thresholds mark the upper and lower flow limits of the ischemic penumbra which is thought to suffer only functional but not structural injury. Recent studies of the functional and metabolic disturbances suggest a more complex pattern of thresholds. At declining flow rates, protein synthesis is inhibited at first (at a thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
786
3
36

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,275 publications
(856 citation statements)
references
References 80 publications
24
786
3
36
Order By: Relevance
“…Annexin 2, a phospholipid-binding protein found on cell surface, has been identified as a coreceptor for both plasminogen and t-PA (Hajjar and Hamel, 1990, 1991, 1994. We have previously shown that annexin 2 is attached to endothelial cells in a calcium-dependent manner and fibrinolytic activity disappears in the absence of calcium (Ishii et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Annexin 2, a phospholipid-binding protein found on cell surface, has been identified as a coreceptor for both plasminogen and t-PA (Hajjar and Hamel, 1990, 1991, 1994. We have previously shown that annexin 2 is attached to endothelial cells in a calcium-dependent manner and fibrinolytic activity disappears in the absence of calcium (Ishii et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Brain tissues with perfusion deficits below a critical threshold (Hossmann, 1994) experience metabolic energy failure, membrane depolarization and subsequent cellular swelling. These changes precipitate a reduction in the apparent diffusion coefficient (ADC) of brain water and are manifested as hyperintense regions on DWI (Busch et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Overview of ischemia-pathophysiology: topics and targets of neuroprotection Subject Selected Reviews General review articles (Siesjo, 1981 (Koehler, 1998;Ginsberg et al, 1998b) Transgenic and knockout mouse models (Chan et al, 1995;Liang et al, 2004) In vitro modeling of "ischemia": hippocampal slice preparation (Noraberg et al, 2005) Cerebral blood flow-determined thresholds of ischemic injury (Heiss et al, 1983;Hossmann, 1994b) Ischemic neuropathology (Graham, 1992) Selective vulnerability; delayed ischemic injury (Wieloch, 1985;Ginsberg, 1990 …”
mentioning
confidence: 99%
“…This disruption in ionic equilibrium, combined with the continued hypoxia and hypoglycemia, leads to a secondary stage of neuronal damage that progressively spreads to neurons located adjacent to, and well outside of, the core region (Lipton, 1999;Zheng et al, 2003;Brouns and De Deyn, 2009). This region is called the "penumbra" and is characterized by metabolic arrest, cellular stress and eventual death of neurons primarily via apoptosis (Astrup et al, 1981;Hossmann, 1994;Lipton, 1999). Together, the core and penumbra * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%